Novel Anti-Interleukin-1β Therapy Preserves Retinal Integrity: A Longitudinal Investigation Using OCT Imaging and Automated Retinal Segmentation in Small Rodents - Sayah, Diane N.; Zhou, Tianwei E.; Omri, Samy; Mazzaferri, Javier; Quiniou, Christiane; Wirth, Maëlle; Côté, France; Dabouz, Rabah; Desjarlais, Michel; Costantino, Santiago; Chemtob, Sylvain (Frontiers in Pharmacology, 2020)
Abstract Retinopathy of prematurity (ROP) is the leading cause of blindness in neonates. Inflammation, in particular Interleukin-1β (IL-1β), is increased in early stages of the disorder, and contributes to inner and outer retinal vasoobliteration in the Oxygen-Induced Retinopathy (OIR) model of ROP. A small peptide antagonist of IL-1 receptor, composed of the amino acid sequence, rytvela, has been shown to exert beneficial anti-inflammatory effects without compromising immunovigilance-related NF-κB in reproductive tissues. We conducted a longitudinal study to determine the efficacy of ‘rytvela’ in preserving the integrity of the retina in OIR model, using optical coherence tomography (OCT) which provides high-resolution cross-sectional imaging of ocular structures in vivo. Sprague-Dawley rats subjected to OIR and treated or not with ‘rytvela’ were compared to IL-1 receptor antagonist (Kineret). OCT imaging and custom automated segmentation algorithm used to measure retinal thickness were obtained at P14 and P30; gold-standard immunohistochemistry (IHC) was used to confirm retinal anatomical changes. OCT revealed significant retinal thinning in untreated animals by P30, confirmed by IHC; these changes were coherently associated with increased apoptosis. Both rytvela and Kineret subsided apoptosis and preserved retinal thickness. As anticipated, Kineret diminished both SAPK/JNK and NF-κB axes, whereas rytvela selectively abated the former which resulted in preserved monocyte phagocytic function. Altogether, OCT imaging with automated segmentation is a reliable non-invasive approach to study longitudinally retinal pathology in small animal models of retinopathy.